MODERNIZATION OF THE EXTRUDER WORM WITH THE PURPOSE OF IMPROVING THE EFFICIENCY OF MATERIAL MIXING IN THE MANUFACTURE OF POLYMER PRODUCTS (World Science, 2022)
The study selected a technical solution to improve the mixing of polymeric materials in the extruder with the modernization of the worm based on the execution of a detachable mixing and dispersing section. It is formed by a pair of elements, each in the form of a cylinder with coots evenly made along the side surface inclined towards one of its bases, converging to nothing. This design of the extruder worm eliminates the formation of stagnant zones, but also due to the alternation in the circular direction of each element of the specified section of the annular sections and sections in the form of circular segments, it provides a high mixing and dispersing effect of the machine as a whole.